Water-resistant and moisture-proof corrugated paper base paper and processing technology thereof

By adding enzymatic treatment and enhancer to the corrugated paper processing technology and applying multi-component surface glue agent to the surface, the problem of insufficient water resistance and moisture resistance of corrugated paper is solved, significantly improving the water resistance and mechanical properties of the paper, and avoiding the strength drop and damage caused by water absorption of packaging materials.

CN119800758APending Publication Date: 2025-04-11JIANGSU HAOTIAN KRAFT PAPER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411827983.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The water and moisture resistance of corrugated cardboard is insufficient, resulting in softening of packaging materials and decreasing strength, which in turn causes packaging damage and other problems.

Method used

A water-resistant and moisture-resistant corrugated paper processing technology is adopted, including waste paper screening and crushing and mixing with deionized water, adding bleach additives and enzymes for processing, forming an enzymatic slurry, and then mixing with reinforcement to form, dehydrating, and then drying through extrusion and pressing, multi-component surface applicator on the surface and drying, obtaining water-resistant moisture-resistant corrugated paper.

Benefits of technology

It improves the water resistance and mechanical properties of corrugated paper, enhances the tensile strength and ring compressive strength of the paper, reduces water absorption, and effectively avoids the strength reduction and damage caused by water absorption of packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005184835930000151
    Figure BDA0005184835930000151
Patent Text Reader

Abstract

The invention relates to the technical field of corrugated paper base paper, and particularly discloses waterproof and moistureproof corrugated paper base paper and a processing technology thereof.Waste paper is made into paper pulp, the paper pulp is subjected to enzymolysis treatment through pectinase and laccase, a polyamide type reinforcing agent grafted with quaternary ammonium salt chitosan is added, and after the paper pulp is put on a net to form paper, the water-resistant and moistureproof corrugated paper base paper is obtained. The surface of the corrugated paper is coated with a polyvinyl alcohol type sizing agent containing diacetylmonoxime-terminated isocyanate groups and an organic titanium cross-linking agent, the water-resistant and moisture-proof corrugated paper base paper is obtained, and the corrugated paper base paper is excellent in mechanical property and good in waterproof effect and meets the requirements of actual production and use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of corrugated paper base paper, in particular to water-resistant and moisture-proof corrugated paper base paper and a processing technology thereof. Background Art

[0002] With the advancement of science and technology and the development of society, people's demand for logistics and packaging industries is also deepening. Among the many packaging materials, corrugated paperboard has gradually replaced wood boards and other packaging materials with its advantages of light weight, low price, easy processing, and strong adaptability, becoming the first choice for logistics and packaging industries. As the main material for manufacturing corrugated paperboard, the quality of corrugated paperboard directly affects the performance of corrugated paperboard. In actual use, due to the influence of factors such as transportation distance, storage method, and environment, moisture in the air can easily penetrate into the corrugated paperboard, causing the corrugated paperboard to become soft and the strength to decrease, which in turn causes packaging damage and other problems. Therefore, it is necessary to develop waterproof and moisture-proof corrugated paperboard to solve the problems of packaging damage caused by the poor water resistance and moisture resistance of corrugated paperboard packaging materials. Summary of the invention

[0003] The purpose of the present invention is to provide a water-resistant and moisture-proof corrugated paper base paper and a processing technology thereof, so as to solve the problem that the water resistance and moisture resistance of the corrugated paperboard are not good enough.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A water-resistant and moisture-proof corrugated paper base paper processing process, specifically comprising:

[0006] Step (1): after screening and crushing the waste paper, mixing it with deionized water, adding a bleaching aid, stirring evenly, soaking for 3 to 5 hours and then dissociating it to obtain a waste paper pulp;

[0007] Step (2): screening the waste paper pulp to remove large debris and plastic impurities, and then performing enzymatic hydrolysis to obtain enzymatic hydrolysis pulp;

[0008] Step: (3): the enzymatic slurry is mixed with a reinforcing agent, sprayed onto a mesh surface for forming, and then squeezed, pressed, dehydrated, and dried to obtain recycled base paper;

[0009] Step (4): After coating the surface of the recycled base paper with a multi-component surface sizing agent, drying and packaging, water-resistant and moisture-proof corrugated paper is obtained.

[0010] As a limitation of the present invention, the bleaching aid contains, by mass fraction, 50-55% sodium hydroxide, 25-30% sodium dodecyl sulfate, and 10-15% fatty alcohol polyoxyethylene ether.

[0011] As a limitation of the present invention, step (2) is specifically:

[0012] The waste paper pulp is sieved to screen out large debris and plastic impurities, mixed with deionized water, and the pH is adjusted. Pectinase is added for pretreatment at 43-48°C for 50-70 minutes. After the pretreatment is completed, laccase and glutamic acid are added for enzymatic hydrolysis reaction. The reaction time is 150-170 minutes. After the reaction is completed, the temperature is raised to 100-105°C for inactivation, and filtered to obtain enzymatic slurry.

[0013] As a limitation of the present invention, the mass ratio of waste paper pulp, pectinase, laccase and glutamic acid is (450-550):(0.04-0.06):(5.5-5.6):(4.5-5.5).

[0014] As a limitation of the present invention, the preparation method of the enhancer is:

[0015] 2,3-Epoxypropyltrimethylammonium chloride and isopropanol are mixed and stirred to obtain epoxypropyltrimethylammonium chloride solution, chitosan is added to 2% acetic acid solution, stirred to obtain chitosan, and after chitosan is completely dissolved, sodium hydroxide solution is added to adjust the pH to 8-10, the mixture is allowed to stand for 7-9 hours, filtered, the filter residue is washed with deionized water until it is neutral, mixed with isopropanol, stirred to obtain epoxypropyltrimethylammonium chloride solution at 70-90°C and kept warm for reaction for 10-14 hours, anhydrous ethanol is added after the reaction is completed, precipitation is carried out, filtered, the filter residue is washed with anhydrous ethanol, and vacuum dried at 60-70°C to obtain quaternary ammonium salt chitosan;

[0016] Mix quaternary ammonium salt chitosan with acetic acid, stir evenly, add adipic acid, diethylenetriamine, glycidyl methacrylate and propylene glycol after they are completely dissolved, stir evenly, heat to 75-85°C, add ammonium cerium nitrate and deionized water to initiate the reaction, heat to 105-115°C, react for 3-5 hours, cool to room temperature after the reaction is completed, and obtain an enhancer.

[0017] As a limitation of the present invention, in the reinforcing agent, the amounts of the components are as follows, by weight: 0.8 to 1.2 parts of quaternary ammonium salt chitosan, 14.0 to 15.0 parts of adipic acid, 11.0 to 12.0 parts of diethylenetriamine, and 12.5 to 13.0 parts of methyl methacrylate.

[0018] As a limitation of the present invention, the preparation method of the multi-component surface sizing agent is:

[0019] Mix polyvinyl alcohol and N,N-dimethylformamide, fully dissolve at 85-95°C for 3-5 hours to obtain a polyvinyl alcohol solution, mix butanone oxime and isophorone diisocyanate, stir evenly, add dibutyltin dilaurate, react at 50-70°C and 150-300rpm for 2-4 hours, cool to 30-50°C after the reaction is completed, add polyvinyl alcohol solution, react at 30-50°C and 150-300rpm for 20-40 minutes to obtain isocyanate cross-linked polyvinyl alcohol;

[0020] Mix ethylene glycol, lactic acid, propylene glycol and butyl titanate, react at 75-85° C. for 1-3 hours, and cool after the reaction to obtain an organic titanium crosslinking agent;

[0021] Mix polyvinyl alcohol and deionized water, stir evenly, raise the temperature to 85-95° C., heat for 4-6 hours to fully dissolve, add isocyanate cross-linked polyvinyl alcohol, glycerol, organic titanium cross-linking agent and deionized water after dissolution, stir evenly to obtain a multi-component surface sizing agent.

[0022] As a limitation of the present invention, in the organic titanium crosslinking agent, the amounts of the components are as follows, by weight: 11.0 to 13.0 parts of ethylene glycol, 4.0 to 5.0 parts of lactic acid, 1.0 to 2.0 parts of propylene glycol, and 1.0 to 3.0 parts of butyl titanate.

[0023] As a limitation of the present invention, in the multi-component surface sizing agent, the amounts of the components are as follows, by weight: 0.2 to 0.6 parts of polyvinyl alcohol, 0.8 to 1.2 parts of isocyanate cross-linked polyvinyl alcohol, 0.5 to 1.5 parts of glycerol, and 0.3 to 0.7 parts of an organic titanium cross-linking agent.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] By treating waste paper pulp with pectinase and laccase together, the lignin phenolic hydroxyl groups are converted into free radicals. The combination between them can increase the binding force between fibers, increase the kink index of pulp fibers, and make the binding ability between fibers better, thereby improving the strength and mechanical properties of pulp paper. The lignin oxidized by laccase can undergo an addition reaction with glutamic acid, increasing the carboxyl content in pulp fibers, thereby improving the strength and mechanical properties of pulp paper.

[0026] The chitosan quaternary ammonium salt molecules are introduced into the polyamide structure of hexamethylenediamine and diethylenetriamine copolymers. The chitosan quaternary ammonium salt molecules can be adsorbed together with the pulp fibers through electrostatic adsorption, thereby increasing the number of hydrogen bonds. At the same time, the polyamide structure increases its molecular weight and degree of branching, thereby enhancing the mechanical properties of pulp paper. The copolymerization product of chitosan and polyacrylamide contains a large number of amino groups in the molecules, which can form a strong ionic bond with the carboxyl groups on the surface of the pulp fibers, thereby improving the mechanical properties of pulp paper.

[0027] In polyvinyl alcohol, butanone oxime-terminated isocyanate groups are introduced and an organic titanium crosslinking agent is added. After high-temperature drying, the highly active isocyanate groups blocked by butanone oxime undergo a deblocking reaction. The highly active isocyanate groups undergo chemical crosslinking with the fibers, polyvinyl alcohol and pulp fibers produce hydrogen bonds, and organic titanium forms a coordination complex between pulp fibers and polyvinyl alcohol, forming a multiple crosslinked network structure between paper fibers, which can effectively improve the mechanical properties and waterproof properties of paper. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Waste paper (national waste COCC12#), pectinase (1.1×10 6 U / L), laccase (3×10 4 U / g), polyvinyl alcohol (Xn=1700).

[0030] Embodiment 1: A processing technology for water-resistant and moisture-proof corrugated paper, specifically comprising:

[0031] Step 1: 500 g of waste paper was screened and crushed, mixed with 5 L of deionized water, added with 50 g of bleaching aid, stirred evenly, and soaked for 4 hours to dissociate to obtain waste paper pulp;

[0032] Step 2: 500 g of waste paper pulp was sieved to remove large debris and plastic impurities, and then mixed with 5 L of deionized water, and the pH was adjusted to 6.0. At 45° C., 0.05 g of pectinase was added for enzymolysis for 60 min, and then 5.54 g of laccase and 5 g of glutamic acid were added for reaction for 160 min. After the reaction was completed, the temperature was raised to 100° C. for inactivation, and filtered to obtain enzymolysis slurry;

[0033] Step 3: After 500g of enzymatic slurry is evenly mixed with 3g of reinforcing agent, the mixture is sprayed onto the mesh surface to form, and then the mixture is squeezed, dehydrated and dried to obtain recycled base paper;

[0034] Step 4: Place the recycled base paper on a roller coater, use a sizing roller to evenly coat the multi-component surface sizing agent on the recycled base paper at a speed of 4.0 mm / s, and use a scraper to scrape away excess multi-component surface sizing agent. After coating, dry at 110°C and pack into rolls to obtain water-resistant and moisture-proof corrugated paper.

[0035] Wherein, the preparation method of the enhancer is:

[0036] Mix 9g of 2,3-epoxypropyltrimethylammonium chloride with 100mL of isopropanol, stir evenly to obtain a epoxypropyltrimethylammonium chloride solution, add 2g of chitosan to 100mL of 2% acetic acid solution, stir evenly, add sodium hydroxide solution to adjust the pH to 9 after complete dissolution, let stand for 8h, filter, wash the filter residue with deionized water until neutral, mix with 15mL of isopropanol, stir evenly, add epoxypropyltrimethylammonium chloride solution at 80°C and keep warm for reaction for 12h, after the reaction is completed, add 150mL of anhydrous ethanol, precipitate, filter, wash the filter residue with anhydrous ethanol, and vacuum dry at 65°C to obtain quaternary ammonium salt chitosan;

[0037] Mix 1g of quaternary ammonium salt chitosan with 1mL of acetic acid, stir evenly, add 14.6g of adipic acid, 11.3g of diethylenetriamine, 12.8g of glycidyl methacrylate and 25mL of propylene glycol after complete dissolution, stir evenly, heat to 80°C, add 1.16g of ammonium cerium nitrate and 25mL of deionized water to initiate the reaction, heat to 110°C, react for 4h, cool to room temperature after the reaction is completed, and obtain an enhancer.

[0038] The preparation method of the multi-component surface sizing agent is:

[0039] 9 g of polyvinyl alcohol and 41 g of N,N-dimethylformamide were mixed and fully dissolved at 90° C. for 4 h to obtain a polyvinyl alcohol solution, 1.12 g of butanone oxime and 1.8 g of isophorone diisocyanate were mixed and stirred evenly, 0.06 g of dibutyltin dilaurate was added, and the mixture was reacted at 60° C. and 200 rpm for 3 h. After the reaction was completed, the mixture was cooled to 40° C., the polyvinyl alcohol solution was added, and the mixture was reacted at 40° C. and 200 rpm for 30 min to obtain isocyanate-crosslinked polyvinyl alcohol;

[0040] 12 g of ethylene glycol, 4.5 g of lactic acid, 1.5 g of propylene glycol, and 2 g of butyl titanate were mixed, reacted at 80° C. for 2 h, and cooled after the reaction was completed to obtain an organic titanium crosslinking agent;

[0041] Mix 0.4 g of polyvinyl alcohol and 3.6 g of deionized water, stir evenly, raise the temperature to 90°C, and heat for 5 hours to fully dissolve. After dissolution, add 1 g of isocyanate cross-linked polyvinyl alcohol, 1 g of glycerol, 0.5 g of organic titanium cross-linking agent and 93.5 g of deionized water, stir evenly, and obtain a multi-component surface sizing agent.

[0042] Embodiment 2: A processing technology for water-resistant and moisture-proof corrugated paper, specifically comprising:

[0043] Step 1: 500 g of waste paper was screened and crushed, mixed with 5 L of deionized water, added with 50 g of bleaching aid, stirred evenly, and soaked for 4 hours to dissociate to obtain waste paper pulp;

[0044] Step 2: 500 g of waste paper pulp was sieved to remove large debris and plastic impurities, and then mixed with 5 L of deionized water, and the pH was adjusted to 6.0. At 45° C., 0.05 g of pectinase was added for enzymolysis for 60 min, and then 5.54 g of laccase and 5 g of glutamic acid were added for reaction for 160 min. After the reaction was completed, the temperature was raised to 100° C. for inactivation, and filtered to obtain enzymolysis slurry;

[0045] Step 3: After 500g of enzymatic slurry is evenly mixed with 3g of reinforcing agent, the mixture is sprayed onto the mesh surface to form, and then the mixture is squeezed, dehydrated and dried to obtain recycled base paper;

[0046] Step 4: Place the recycled base paper on a roller coater, use a sizing roller to evenly coat the multi-component surface sizing agent on the recycled base paper at a speed of 4.0 mm / s, and use a scraper to scrape away excess multi-component surface sizing agent. After coating, dry at 110°C and pack into rolls to obtain water-resistant and moisture-proof corrugated paper.

[0047] Wherein, the preparation method of the enhancer is:

[0048] Mix 9g of 2,3-epoxypropyltrimethylammonium chloride with 100mL of isopropanol, stir evenly to obtain a epoxypropyltrimethylammonium chloride solution, add 2g of chitosan to 100mL of 2% acetic acid solution, stir evenly, add sodium hydroxide solution to adjust the pH to 9 after complete dissolution, let stand for 8h, filter, wash the filter residue with deionized water until neutral, mix with 15mL of isopropanol, stir evenly, add epoxypropyltrimethylammonium chloride solution at 80°C and keep warm for reaction for 12h, after the reaction is completed, add 150mL of anhydrous ethanol, precipitate, filter, wash the filter residue with anhydrous ethanol, and vacuum dry at 65°C to obtain quaternary ammonium salt chitosan;

[0049] Mix 0.8g of quaternary ammonium salt chitosan with 1mL of acetic acid, stir evenly, add 14.0g of adipic acid, 11.0g of diethylenetriamine, 12.5g of glycidyl methacrylate and 25mL of propylene glycol after complete dissolution, stir evenly, heat to 80°C, add 1.16g of ammonium cerium nitrate and 25mL of deionized water to initiate the reaction, heat to 110°C, react for 4h, cool to room temperature after the reaction is completed, and obtain an enhancer.

[0050] The preparation method of the multi-component surface sizing agent is:

[0051] 9 g of polyvinyl alcohol and 41 g of N,N-dimethylformamide were mixed and fully dissolved at 90° C. for 4 h to obtain a polyvinyl alcohol solution, 1.12 g of butanone oxime and 1.8 g of isophorone diisocyanate were mixed and stirred evenly, 0.06 g of dibutyltin dilaurate was added, and the mixture was reacted at 60° C. and 200 rpm for 3 h. After the reaction was completed, the mixture was cooled to 40° C., the polyvinyl alcohol solution was added, and the mixture was reacted at 40° C. and 200 rpm for 30 min to obtain isocyanate-crosslinked polyvinyl alcohol;

[0052] 12 g of ethylene glycol, 4.5 g of lactic acid, 1.5 g of propylene glycol, and 2 g of butyl titanate were mixed, reacted at 80° C. for 2 h, and cooled after the reaction was completed to obtain an organic titanium crosslinking agent;

[0053] Mix 0.2 g of polyvinyl alcohol and 3.8 g of deionized water, stir evenly, raise the temperature to 90°C, and heat for 5 hours to fully dissolve. After dissolution, add 0.8 g of isocyanate cross-linked polyvinyl alcohol, 0.5 g of glycerol, 0.3 g of organic titanium cross-linking agent and 94.4 g of deionized water, stir evenly, and obtain a multi-component surface sizing agent.

[0054] Embodiment 3: A processing technology for water-resistant and moisture-proof corrugated paper, specifically comprising:

[0055] Step 1: 500 g of waste paper was screened and crushed, mixed with 5 L of deionized water, added with 50 g of bleaching aid, stirred evenly, and soaked for 4 hours to dissociate to obtain waste paper pulp;

[0056] Step 2: 500 g of waste paper pulp was sieved to remove large debris and plastic impurities, and then mixed with 5 L of deionized water, and the pH was adjusted to 6.0. At 45° C., 0.05 g of pectinase was added for enzymolysis for 60 min, and then 5.54 g of laccase and 5 g of glutamic acid were added for reaction for 160 min. After the reaction was completed, the temperature was raised to 100° C. for inactivation, and filtered to obtain enzymolysis slurry;

[0057] Step 3: 500g of enzymatic slurry is mixed evenly with 3g of reinforcing agent, and then sprayed onto the mesh surface to form, and then squeezed, pressed, dehydrated, and dried to obtain recycled base paper;

[0058] Step 4: Place the recycled base paper on a roller coater, use a sizing roller to evenly coat the multi-component surface sizing agent on the recycled base paper at a speed of 4.0 mm / s, and use a scraper to scrape away excess multi-component surface sizing agent. After coating, dry at 110°C and pack into rolls to obtain water-resistant and moisture-proof corrugated paper.

[0059] Wherein, the preparation method of the enhancer is:

[0060] Mix 9g of 2,3-epoxypropyltrimethylammonium chloride with 100mL of isopropanol, stir evenly to obtain a epoxypropyltrimethylammonium chloride solution, add 2g of chitosan to 100mL of 2% acetic acid solution, stir evenly, add sodium hydroxide solution to adjust the pH to 9 after complete dissolution, let stand for 8h, filter, wash the filter residue with deionized water until neutral, mix with 15mL of isopropanol, stir evenly, add epoxypropyltrimethylammonium chloride solution at 80°C and keep warm for reaction for 12h, after the reaction is completed, add 150mL of anhydrous ethanol, precipitate, filter, wash the filter residue with anhydrous ethanol, and vacuum dry at 65°C to obtain quaternary ammonium salt chitosan;

[0061] Mix 1.0g of quaternary ammonium salt chitosan with 1mL of acetic acid, stir evenly, add 15.0g of adipic acid, 12.0g of diethylenetriamine, 13.0g of glycidyl methacrylate and 25mL of propylene glycol after complete dissolution, stir evenly, heat to 80°C, add 1.16g of ammonium cerium nitrate and 25mL of deionized water to initiate the reaction, heat to 110°C, react for 4h, cool to room temperature after the reaction is completed, and obtain an enhancer.

[0062] The preparation method of the multi-component surface sizing agent is:

[0063] 9 g of polyvinyl alcohol and 41 g of N,N-dimethylformamide were mixed and fully dissolved at 90° C. for 4 h to obtain a polyvinyl alcohol solution, 1.12 g of butanone oxime and 1.8 g of isophorone diisocyanate were mixed and stirred evenly, 0.06 g of dibutyltin dilaurate was added, and the mixture was reacted at 60° C. and 200 rpm for 3 h. After the reaction was completed, the mixture was cooled to 40° C., the polyvinyl alcohol solution was added, and the mixture was reacted at 40° C. and 200 rpm for 30 min to obtain isocyanate-crosslinked polyvinyl alcohol;

[0064] 12 g of ethylene glycol, 4.5 g of lactic acid, 1.5 g of propylene glycol, and 2 g of butyl titanate were mixed, reacted at 80° C. for 2 h, and cooled after the reaction was completed to obtain an organic titanium crosslinking agent;

[0065] Mix 0.6 g of polyvinyl alcohol and 3.4 g of deionized water, stir evenly, heat to 90°C, and heat for 5 hours to fully dissolve. After dissolution, add 1.2 g of isocyanate cross-linked polyvinyl alcohol, 1.5 g of glycerol, 0.7 g of organic titanium cross-linking agent and 92.6 g of deionized water, stir evenly, and obtain a multi-component surface sizing agent.

[0066] Based on Example 1, control experiments were carried out, specifically Comparative Example 1, Comparative Example 2 and Comparative Example 3, as described below:

[0067] Comparative Example 1: This comparative example relates to a processing technology for water-resistant and moisture-proof corrugated paper. The difference from Example 1 is that a polyvinyl alcohol aqueous solution is used as a surface sizing agent, specifically:

[0068] Step 1: 500 g of waste paper was screened and crushed, mixed with 5 L of deionized water, added with 50 g of bleaching aid, stirred evenly, and soaked for 4 hours to dissociate to obtain waste paper pulp;

[0069] Step 2: 500 g of waste paper pulp was sieved to remove large debris and plastic impurities, and then mixed with 5 L of deionized water, and the pH was adjusted to 6.0. At 45° C., 0.05 g of pectinase was added for enzymolysis for 60 min, and then 5.54 g of laccase and 5 g of glutamic acid were added for reaction for 160 min. After the reaction was completed, the temperature was raised to 100° C. for inactivation, and filtered to obtain enzymolysis slurry;

[0070] Step 3: 500g of enzymatic slurry is mixed evenly with 3g of reinforcing agent, and then sprayed onto the mesh surface to form, and then squeezed, pressed, dehydrated, and dried to obtain recycled base paper;

[0071] Step 4: Place the recycled base paper on a roller coater, use a sizing roller to evenly coat the surface sizing agent on the recycled base paper at a speed of 4.0 mm / s, and use a scraper to scrape off excess surface sizing agent. After coating, dry at 110°C and pack into rolls to obtain water-resistant and moisture-proof corrugated paper.

[0072] Wherein, the preparation method of the enhancer is:

[0073] Mix 9g of 2,3-epoxypropyltrimethylammonium chloride with 100mL of isopropanol, stir evenly to obtain a epoxypropyltrimethylammonium chloride solution, add 2g of chitosan to 100mL of 2% acetic acid solution, stir evenly, add sodium hydroxide solution to adjust the pH to 9 after complete dissolution, let stand for 8h, filter, wash the filter residue with deionized water until neutral, mix with 15mL of isopropanol, stir evenly, add epoxypropyltrimethylammonium chloride solution at 80°C and keep warm for reaction for 12h, after the reaction is completed, add 150mL of anhydrous ethanol, precipitate, filter, wash the filter residue with anhydrous ethanol, and vacuum dry at 65°C to obtain quaternary ammonium salt chitosan;

[0074] Mix 1g of quaternary ammonium salt chitosan with 1mL of acetic acid, stir evenly, add 14.6g of adipic acid, 11.3g of diethylenetriamine, 12.8g of glycidyl methacrylate and 25mL of propylene glycol after complete dissolution, stir evenly, heat to 80°C, add 1.16g of ammonium cerium nitrate and 25mL of deionized water to initiate the reaction, heat to 110°C, react for 4h, cool to room temperature after the reaction is completed, and obtain an enhancer.

[0075] The preparation method of the surface sizing agent is:

[0076] Mix 5 g of polyvinyl alcohol and 95 g of deionized water, stir evenly, heat to 90° C., and heat for 5 h to fully dissolve to obtain a multi-component surface sizing agent.

[0077] Comparative Example 2: This comparative example relates to a processing technology for water-resistant and moisture-proof corrugated paper. The difference from Example 1 is that no reinforcing agent is added, specifically:

[0078] Step 1: 500 g of waste paper was screened and crushed, mixed with 5 L of deionized water, added with 50 g of bleaching aid, stirred evenly, and soaked for 4 hours to dissociate to obtain waste paper pulp;

[0079] Step 2: 500 g of waste paper pulp was sieved to remove large debris and plastic impurities, and then mixed with 5 L of deionized water, and the pH was adjusted to 6.0. At 45° C., 0.05 g of pectinase was added for enzymolysis for 60 min, and then 5.54 g of laccase and 5 g of glutamic acid were added for reaction for 160 min. After the reaction was completed, the temperature was raised to 100° C. for inactivation, and filtered to obtain enzymolysis slurry;

[0080] Step 3: Spray 500g of the enzymatic slurry onto the mesh surface to form it, and then squeeze, dehydrate and dry it to obtain recycled base paper;

[0081] Step 4: Place the recycled base paper on a roller coater, use a sizing roller to evenly coat the multi-component surface sizing agent on the recycled base paper at a speed of 4.0 mm / s, and use a scraper to scrape away excess multi-component surface sizing agent. After coating, dry at 110°C and pack into rolls to obtain water-resistant and moisture-proof corrugated paper.

[0082] Wherein, the preparation method of the multi-component surface sizing agent is:

[0083] 9 g of polyvinyl alcohol and 41 g of N,N-dimethylformamide were mixed and fully dissolved at 90° C. for 4 h to obtain a polyvinyl alcohol solution, 1.12 g of butanone oxime and 1.8 g of isophorone diisocyanate were mixed and stirred evenly, 0.06 g of dibutyltin dilaurate was added, and the mixture was reacted at 60° C. and 200 rpm for 3 h. After the reaction was completed, the mixture was cooled to 40° C., the polyvinyl alcohol solution was added, and the mixture was reacted at 40° C. and 200 rpm for 30 min to obtain isocyanate-crosslinked polyvinyl alcohol;

[0084] 12 g of ethylene glycol, 4.5 g of lactic acid, 1.5 g of propylene glycol, and 2 g of butyl titanate were mixed, reacted at 80° C. for 2 h, and cooled after the reaction was completed to obtain an organic titanium crosslinking agent;

[0085] Mix 0.4 g of polyvinyl alcohol and 3.6 g of deionized water, stir evenly, raise the temperature to 90°C, and heat for 5 hours to fully dissolve. After dissolution, add 1 g of isocyanate cross-linked polyvinyl alcohol, 1 g of glycerol, 0.5 g of organic titanium cross-linking agent and 93.5 g of deionized water, stir evenly, and obtain a multi-component surface sizing agent.

[0086] Comparative Example 3: This comparative example relates to a processing technology for water-resistant and moisture-proof corrugated paper, which differs from Example 1 in that no enzymatic treatment is performed, specifically:

[0087] Step 1: 500 g of waste paper was screened and crushed, mixed with 5 L of deionized water, added with 50 g of bleaching aid, stirred evenly, and soaked for 4 hours to dissociate to obtain waste paper pulp;

[0088] Step 2: 500g of waste paper pulp is sieved to remove large debris and plastic impurities, then mixed evenly with 3g of reinforcing agent, sprayed onto the mesh surface for forming, and then squeezed, pressed, dehydrated, and dried to obtain recycled base paper;

[0089] Step 3: Place the recycled base paper on a roller coater, use a sizing roller to evenly coat the multi-component surface sizing agent on the recycled base paper at a speed of 4.0 mm / s, and use a scraper to scrape away excess multi-component surface sizing agent. After coating, dry at 110°C and pack into rolls to obtain water-resistant and moisture-proof corrugated paper.

[0090] Wherein, the preparation method of the enhancer is:

[0091] Mix 9g of 2,3-epoxypropyltrimethylammonium chloride with 100mL of isopropanol, stir evenly to obtain a epoxypropyltrimethylammonium chloride solution, add 2g of chitosan to 100mL of 2% acetic acid solution, stir evenly, add sodium hydroxide solution to adjust the pH to 9 after complete dissolution, let stand for 8h, filter, wash the filter residue with deionized water until neutral, mix with 15mL of isopropanol, stir evenly, add epoxypropyltrimethylammonium chloride solution at 80°C and keep warm for reaction for 12h, after the reaction is completed, add 150mL of anhydrous ethanol, precipitate, filter, wash the filter residue with anhydrous ethanol, and vacuum dry at 65°C to obtain quaternary ammonium salt chitosan;

[0092] Mix 1g of quaternary ammonium salt chitosan with 1mL of acetic acid, stir evenly, add 14.6g of adipic acid, 11.3g of diethylenetriamine, 12.8g of glycidyl methacrylate and 25mL of propylene glycol after complete dissolution, stir evenly, heat to 80°C, add 1.16g of ammonium cerium nitrate and 25mL of deionized water to initiate the reaction, heat to 110°C, react for 4h, cool to room temperature after the reaction is completed, and obtain an enhancer.

[0093] The preparation method of the multi-component surface sizing agent is:

[0094] 9 g of polyvinyl alcohol and 41 g of N,N-dimethylformamide were mixed and fully dissolved at 90° C. for 4 h to obtain a polyvinyl alcohol solution, 1.12 g of butanone oxime and 1.8 g of isophorone diisocyanate were mixed and stirred evenly, 0.06 g of dibutyltin dilaurate was added, and the mixture was reacted at 60° C. and 200 rpm for 3 h. After the reaction was completed, the mixture was cooled to 40° C., the polyvinyl alcohol solution was added, and the mixture was reacted at 40° C. and 200 rpm for 30 min to obtain isocyanate-crosslinked polyvinyl alcohol;

[0095] 12 g of ethylene glycol, 4.5 g of lactic acid, 1.5 g of propylene glycol, and 2 g of butyl titanate were mixed, reacted at 80° C. for 2 h, and cooled after the reaction was completed to obtain an organic titanium crosslinking agent;

[0096] Mix 0.4 g of polyvinyl alcohol and 3.6 g of deionized water, stir evenly, raise the temperature to 90°C, and heat for 5 hours to fully dissolve. After dissolution, add 1 g of isocyanate cross-linked polyvinyl alcohol, 1 g of glycerol, 0.5 g of organic titanium cross-linking agent and 93.5 g of deionized water, stir evenly, and obtain a multi-component surface sizing agent.

[0097] Detection experiment:

[0098] Water-resistant and moisture-proof corrugated paper was processed according to the processing techniques in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3 respectively as the test object of the experiment.

[0099] Water absorption test:

[0100] The test was carried out according to the "Determination of Water Absorption of Paper and Paperboard - Kebo Method" (GB / T 1540-2002). A circular sample was cut from the test object away from the edge using a special sample cutter. The sample diameter was 125 mm. After weighing the mass of the circular sample, the circular sample was placed in a metal cylinder containing 100 mL of deionized water (the inner cross-section of the metal cylinder was 100 cm 2 , height 50mm), turn the metal cylinder 180° and maintain it for 30s, take out the circular sample after 30s, weigh the mass of the circular sample again, and calculate the absorbent water value of the test object.

[0101] Tensile strength test:

[0102] The test is carried out according to "Determination of tensile strength of paper and paperboard - Constant rate loading method" (GB / T 453-2002) and "Determination of tensile strength of paper and paperboard after immersion in water" (GB / T 465.2-2008). A special sample cutter is used to take a horizontal sample away from the edge of the test object. The sample size is 15mm×150mm. The sample is fixed vertically on the fixture of the tensile strength testing machine. The maximum force applied when the sample breaks is recorded to measure the dry tensile strength of the sample. After cutting samples of the same size, the samples are placed in distilled water at room temperature and soaked for 15 minutes. After 15 minutes, the samples are taken out, the moisture on the surface of the samples is absorbed with filter paper, and then they are quickly placed on the fixture of the tensile strength testing machine for measurement to measure the wet tensile strength of the samples.

[0103] Ring compression strength test:

[0104] According to the "Determination of Ring Compression Strength of Paper and Paperboard" (GB / T 2679.8-1995), a special sample cutter is used to take samples horizontally away from the edge of the test object. The size of the sample is 152.0mm×17.0mm. The fixed platen electronic compression instrument is used for the experiment. The sample is fixed on the sample holder, the instrument is started, and the sample is compressed until the sample is crushed. The ring compression strength index of the sample is calculated.

[0105]

[0106] Conclusion: From the test data of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3, it can be seen that the dry tensile strength, wet tensile strength and ring crush strength of the sample of Example 1 are higher than those of the samples of Comparative Example 1, Comparative Example 2 and Comparative Example 3, and the water absorption value is lower than that of the samples processed by the processes of Comparative Example 1, Comparative Example 2 and Comparative Example 3, indicating that the water resistance, tensile strength and ring crush strength of the water-resistant and moisture-proof corrugated paper processed by the process of Example 1 are better than those of the water-resistant and moisture-proof corrugated paper processed by the processes of Comparative Example 1, Comparative Example 2 and Comparative Example 3, and the water-resistant and moisture-proof corrugated paper of the present invention has good water resistance and mechanical properties.

[0107] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A process for processing water-resistant and moisture-proof corrugated paper, characterized in that: Specifically: Step (1): after screening and crushing the waste paper, mixing it with deionized water, adding a bleaching aid, stirring evenly, soaking for 3 to 5 hours and then dissociating it to obtain a waste paper pulp; Step (2): screening the waste paper pulp to remove large debris and plastic impurities, and then performing enzymatic hydrolysis to obtain enzymatic hydrolysis pulp; Step: (3): the enzymatic slurry is mixed with a reinforcing agent, sprayed onto a mesh surface for forming, and then squeezed, pressed, dehydrated, and dried to obtain recycled base paper; Step (4): After coating the surface of the recycled base paper with a multi-component surface sizing agent, drying and packaging, water-resistant and moisture-proof corrugated paper is obtained.

2. The processing technology of a water-resistant and moisture-proof corrugated paper base paper according to claim 1, characterized in that: Calculated by mass fraction, the bleaching aid contains 50-55% sodium hydroxide, 25-30% sodium dodecyl sulfate and 10-15% fatty alcohol polyoxyethylene ether.

3. The processing technology of a water-resistant and moisture-proof corrugated paper base paper according to claim 1, characterized in that: Step (2) is specifically as follows: The waste paper pulp is sieved to screen out large debris and plastic impurities, mixed with deionized water, and the pH is adjusted. Pectinase is added for pretreatment at 43-48°C for 50-70 minutes. After the pretreatment is completed, laccase and glutamic acid are added for enzymatic hydrolysis reaction. The reaction time is 150-170 minutes. After the reaction is completed, the temperature is raised to 100-105°C for inactivation, and filtered to obtain enzymatic slurry.

4. The processing technology of water-resistant and moisture-proof corrugated paper according to claim 3 is characterized in that: The mass ratio of waste paper pulp, pectinase, laccase and glutamic acid is (450-550):(0.04-0.06):(5.5-5.6):(4.5-5.5).

5. The processing technology of water-resistant and moisture-proof corrugated paper according to claim 1, characterized in that: The preparation method of the enhancer is: 2,3-Epoxypropyltrimethylammonium chloride and isopropanol are mixed and stirred to obtain epoxypropyltrimethylammonium chloride solution, chitosan is added to 2% acetic acid solution, stirred to obtain chitosan, and after chitosan is completely dissolved, sodium hydroxide solution is added to adjust the pH to 8-10, the mixture is allowed to stand for 7-9 hours, filtered, the filter residue is washed with deionized water until it is neutral, mixed with isopropanol, stirred to obtain epoxypropyltrimethylammonium chloride solution at 70-90°C and kept warm for reaction for 10-14 hours, anhydrous ethanol is added after the reaction is completed, precipitation is carried out, filtered, the filter residue is washed with anhydrous ethanol, and vacuum dried at 60-70°C to obtain quaternary ammonium salt chitosan; Mix quaternary ammonium salt chitosan with acetic acid, stir evenly, add adipic acid, diethylenetriamine, glycidyl methacrylate and propylene glycol after they are completely dissolved, stir evenly, heat to 75-85°C, add ammonium cerium nitrate and deionized water to initiate the reaction, heat to 105-115°C, react for 3-5 hours, cool to room temperature after the reaction is completed, and obtain an enhancer.

6. The processing technology of water-resistant and moisture-proof corrugated paper according to claim 5, characterized in that: In the enhancer, the amounts of the components are as follows, by weight: 0.8 to 1.2 parts of quaternary ammonium salt chitosan, 14.0 to 15.0 parts of adipic acid, 11.0 to 12.0 parts of diethylenetriamine, and 12.5 to 13.0 parts of methyl methacrylate.

7. The processing technology of water-resistant and moisture-proof corrugated paper according to claim 1, characterized in that: The preparation method of the multi-component surface sizing agent is: Mix polyvinyl alcohol and N,N-dimethylformamide, fully dissolve at 85-95°C for 3-5 hours to obtain a polyvinyl alcohol solution, mix butanone oxime and isophorone diisocyanate, stir evenly, add dibutyltin dilaurate, react at 50-70°C and 150-300rpm for 2-4 hours, cool to 30-50°C after the reaction is completed, add polyvinyl alcohol solution, react at 30-50°C and 150-300rpm for 20-40 minutes to obtain isocyanate cross-linked polyvinyl alcohol; Mix ethylene glycol, lactic acid, propylene glycol and butyl titanate, react at 75-85° C. for 1-3 hours, and cool after the reaction to obtain an organic titanium crosslinking agent; Mix polyvinyl alcohol and deionized water, stir evenly, raise the temperature to 85-95° C., heat for 4-6 hours to fully dissolve, add isocyanate cross-linked polyvinyl alcohol, glycerol, organic titanium cross-linking agent and deionized water after dissolution, stir evenly to obtain a multi-component surface sizing agent.

8. The processing technology of water-resistant and moisture-proof corrugated paper according to claim 7, characterized in that: In terms of parts by mass, the amounts of the components in the organic titanium crosslinking agent are: 11.0 to 13.0 parts of ethylene glycol, 4.0 to 5.0 parts of lactic acid, 1.0 to 2.0 parts of propylene glycol, and 1.0 to 3.0 parts of butyl titanate.

9. The processing technology of water-resistant and moisture-proof corrugated paper according to claim 7, characterized in that: In the multi-component surface sizing agent, the amounts of the components are as follows, by weight: 0.2 to 0.6 parts of polyvinyl alcohol, 0.8 to 1.2 parts of isocyanate cross-linked polyvinyl alcohol, 0.5 to 1.5 parts of glycerol, and 0.3 to 0.7 parts of an organic titanium cross-linking agent.